1998
DOI: 10.1200/jco.1998.16.3.859
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in primary CNS lymphoma.

Abstract: Combined modality therapy for PCNSL has improved survival, but relapse is common and late neurologic toxicity is a significant complication. Although this approach is highly effective for younger patients, efficacious but less neurotoxic regimens need to be developed for older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
283
0
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(301 citation statements)
references
References 13 publications
11
283
0
7
Order By: Relevance
“…9,10 In long-term survivors of brain metastases from systemic cancer, and in patients with primary lymphoma of the central nervous system, treatment with whole-brain radiotherapy can lead to radiation-induced encephalopathy. 11,12 Partly because of these side-effects, standard treatment of glioma patients is based on focal radiotherapy rather than on whole-brain radiotherapy. Apart from a large radiotherapy treatment volume, high radiotherapy total and fraction dose, concomitant chemotherapy, and old age have been identified as potential risk factors for cognitive deterioration in glioma Effect of radiotherapy and other treatment-related factors on mid-term to long-term cognitive sequelae in low-grade gliomas: a comparative study acknowledgments section).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In long-term survivors of brain metastases from systemic cancer, and in patients with primary lymphoma of the central nervous system, treatment with whole-brain radiotherapy can lead to radiation-induced encephalopathy. 11,12 Partly because of these side-effects, standard treatment of glioma patients is based on focal radiotherapy rather than on whole-brain radiotherapy. Apart from a large radiotherapy treatment volume, high radiotherapy total and fraction dose, concomitant chemotherapy, and old age have been identified as potential risk factors for cognitive deterioration in glioma Effect of radiotherapy and other treatment-related factors on mid-term to long-term cognitive sequelae in low-grade gliomas: a comparative study acknowledgments section).…”
Section: Introductionmentioning
confidence: 99%
“…However, like in many other studies, good performance status and young age had a favorable impact on survival 13,24,[39][40][41][42] ; patients who received only symptomatic therapy had shorter survival [18][19][20] and combined chemotherapy and radiotherapy was superior to chemotherapy alone 43 and radiotherapy alone. 44 We observed an estimated median survival of 44 months with combined chemotherapy and radiotherapy compared with a median survival of 9 months with radiotherapy alone and 4 months with chemotherapy alone, which led to fatal complications in 5 of 20 patients (25%).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not significant in our material, the omission of HD MTX in the chemotherapy regimen tended to reduce survival (hazard ratio, 1.50; 95% CI, 0.76-2.96; P 5 .24), which is in accordance with studies that reported a significant impact of HD MTX with hazard ratios of 2.3 29 and 1.48. 44 Despite the therapeutic advances reported from clinical trials the last decades, 17,20 the overall survival of patients who were diagnosed with PCNSL while they remained alive over the 3 5-year periods did not improve over time. This is in accordance with 2 population-based studies from the United States (1975-1999) 14 and Canada (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003), 29 which reported stable outcomes in the periods studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a high incidence of neurotoxicity has been reported in patients receiving radiotherapy, mostly in patients older than 65 years. Up to 35% of patient will present with neurologic deterioration after radiotherapy, leading to a mortality rate of 30% in 5 years 26 . A recent progress is the establishment of a panel of neuropsychological tests to assess, quantify and follow-up treatment-related neurologic deterioration in patients with primary CNS lymphoma.…”
Section: Radiotherapy Might Be More Harmful Than Beneficialmentioning
confidence: 99%